2021
DOI: 10.1007/s10792-021-02051-1
|View full text |Cite
|
Sign up to set email alerts
|

Altered peripapillary vessel density and nerve fiber layer thickness in thyroid-associated ophthalmopathy using optical coherence tomography angiography

Abstract: Objective To measure the peripapillary vessel density (VD) and retinal nerve fiber layer thickness (RNFLT) in thyroid-associated ophthalmopathy (TAO) and dysthyroid optic neuropathy (DON) patients using optical coherence tomography angiography (OCTA), and determine their prognostic relevance. Methods Forty-three TAO patients with or without DON (82 eyes in total) and 26 healthy subjects (52 eyes) were enrolled. All participants underwent ophthalmology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…21 Furthermore, in TAO patients with dysthyroid optic neuropathy (DON), the total peripapillary vessel density and RNFL thickness were significantly lower than those without DON. 22 Since the IOP was higher in the DON group than other groups, high IOP should be as a risk factor for decreased retinal vessel and RNFL thickness in TAO patients. Considering all these findings mentioned above, the changes in retinal vessels and RNFL may mainly result from alterations in hormone levels (especially thyroid hormones) as well as elevated orbital pressure and IOP.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…21 Furthermore, in TAO patients with dysthyroid optic neuropathy (DON), the total peripapillary vessel density and RNFL thickness were significantly lower than those without DON. 22 Since the IOP was higher in the DON group than other groups, high IOP should be as a risk factor for decreased retinal vessel and RNFL thickness in TAO patients. Considering all these findings mentioned above, the changes in retinal vessels and RNFL may mainly result from alterations in hormone levels (especially thyroid hormones) as well as elevated orbital pressure and IOP.…”
Section: Discussionmentioning
confidence: 86%
“…In patients with TAO, significant increases were found in macular and foveal vascular density and perfusion densities, while a significant decrease was found in the foveal avascular zone area when compared with the control group 21 . Furthermore, in TAO patients with dysthyroid optic neuropathy (DON), the total peripapillary vessel density and RNFL thickness were significantly lower than those without DON 22 . Since the IOP was higher in the DON group than other groups, high IOP should be as a risk factor for decreased retinal vessel and RNFL thickness in TAO patients.…”
Section: Discussionmentioning
confidence: 95%
“…They found that VD had no significant relation with different clinical variables [ 17 ]. Jian et al also found that the ONH VD was lower in patients with TED who had optic neuropathy [ 18 ]. In another study by Del Noce et al, there was a significant decrease in the peripapillary choriocapillaris and deep capillary plexus VD in patients with TED compared to healthy age and gender-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…109 Peripapillary vessel density was significantly lower in DON patients in comparison with other TED patients and healthy controls. 110 In a study on 24 eyes of 12 patients, eyes with DON displayed a reduction in (peri)papillary vessel density after decompression surgery more often than eyes without DON, though the small sample size hinders the generalization of the results. 111 Overwhelming evidence for the routine application of optical CT and optical CT-angiography in the diagnosis and management of TED and DON has not yet been delivered, and large, prospective studies exploring these tools are needed.…”
Section: Perimetry Is a Useful Ancillary Test For The Diagnosis And F...mentioning
confidence: 99%